Analysis of Flow Additives in Laser-Based Powder Bed Fusion of Polymers: Implications for Flow Behavior, Processing, Temperature Profile, and Part Characteristics - Cholewa, Simon; Jaksch, Andreas; Drummer, Dietmar (Solid Freeform Fabrication 2023: Proceeding of the 34th Annual International Solid Freeform Fabrication Symposium, 2023)

Coalescence behavior of polyamide 12 as function of zero-shear viscosity and influence on mechanical performance - Cholewa, Simon; Jaksch, Andreas; Drummer, Dietmar (SFF 2022, 2022)
The favored material for powder bed fusion of polymers (PBF-LB/P) is polyamide-12. Its molecular weight increases from post-condensation at elevated temperatures in the building chamber, consequently having different properties when reused. An important aspect of PBF directly affected hereby is the coalescence behavior, as it significantly determines the surface quality, porosity, and thus the component’s mechanical properties. However, detailed studies on coalescence are limited to virgin powders with low viscosity; therefore, coalescence behavior of polyamide-12 with different molecular weights is investigated using hot stage microscopy. Additionally, the zero-shear viscosity is determined using the Carreau model, allowing comparison of experimental results to sintering models. Furthermore, the mechanical properties and surface qualities are analyzed, and components with adequate values are made with two-cycle reprocessed powder. Since surface flaws do not exist uniformly across all components, the orange peel effect is not attributed solely to the increased viscosity of the reused powder.<br
Keywords: Polyamide 12; reused powder; molecular weight; post-condensation

Development of material-adapted processing strategies for laser sintering of polyamide 12 - Greiner, Sandra; Jaksch, Andreas; Cholewa, Simon; Drummer, Dietmar (Advanced Industrial and Engineering Polymer Research, 2021)

Enhancing the Thermal Stability of Polyamide 6 in Powder Bed Fusion via Primary and Secondary Antioxidant Incorporation - Jaksch, Andreas; Cholewa, Simon; Drummer, Dietmar (Solid Freeform Fabrication 2023: Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium – An Additive Manufacturing Conference, 2023)

Experimentelle und simulative Untersuchung der zeit- und ortsaufgelösten Temperaturfelder beim selektiven Strahlschmelzen von Kunststoffen - Greiner, Sandra; Soldner, Dominic; Jaksch, Andreas; Zhao, Meng; Mergheim, Julia; Steinmann, Paul; Wudy, Katrin; Drummer, Dietmar (6. Industriekolloquium des Sonderforschungsbereichs 814, 2018)

Flame-retardant Polyamide 6 for Powder Bed Fusion of Polymers - Cholewa, Simon; Jaksch, Andreas; Drummer, Dietmar (Proceedings of the 19th Rapid.Tech 3D Conference, 2023)

From trash to treasure in additive manufacturing: Recycling of polymer powders by acid catalyzed hydrolysis - Hesse, Nicolas; Jaksch, Andreas; Kaschta, Joachim; Groh, Dominik; Drummer, Dietmar; Peukert, Wolfgang; Schmidt, Jochen (Additive Manufacturing, 2023)
A persistent problem in laser powder bed fusion (PBF) additive manufacturing (AM) of polymers is the accumulation of used feedstock material that cannot be reprocessed due to alterations in the physical and chemical structure upon ageing at elevated temperatures. The chemical ageing of polyamide 12, the most frequently used feedstock in PBF of polymers, occurs due to solid-state post-condensation during the AM process and can be reversed by appropriate processing. This paper investigates the application of acid-catalyzed hydrolytic reconditioning to restore virgin powder properties from used and annealed feedstock material, highlighting a pathway to more sustainability in AM. The proposed method is optimized towards PBF-printing relevant properties and mechanical characteristics of parts build with the recycled feedstock material, which are benchmarked against conventional powder refreshing strategies.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Hydrolysis; Polyamide 12; Polymer ageing; Polymer recycling; Powder bed fusion; Powder characterization

Impact of Layer Time and Hatch Conformity on the Behavior of Thin-Walled Components in Powder Bed Fusion of Polymers - Jaksch, Andreas; Cholewa, Simon; Drummer, Dietmar (AIP Conference Proceedings, 2024)
The effects of process variables like hatch conformity and layer time are often overlooked and, as a result, are not fully understood. This is particularly true for thin-walled components. This work specifically addresses the impact on thin structures, which are critical for maximizing the potential of the laser-based powder bed fusion process. Therefore, tensile specimens of various thicknesses and orientations were manufactured, and the hatch conformity and layer time were altered. For a more profound process understanding, infrared thermography is used to analyze the developing exposure temperatures. While the hatch count indicated an impact on the resulting exposure temperatures, the effect on the resulting part properties is minimal. The layer time shows a notable influence on the part geometry and density. Young’s modulus can be described as constant when considering the mechanical properties, independent of the layer time and hatch conformity. The elongation at break does not influence the hatch conformity but the layer time. Overall, the most significant changes occurred due to variations in the part thickness and must be considered in part optimization.
CRIS-Team Scopus Importer:2025-02-04

Inline Quality Control through Optical Deep Learning-Based Porosity Determination for Powder Bed Fusion of Polymers - Schlicht, Samuel; Jaksch, Andreas; Drummer, Dietmar (Polymers, 2022)
Powder bed fusion of thermoplastic polymers is a powder based additive manufacturing process that allows for manufacturing individualized components with high geometric freedom. Despite achieving higher mechanical properties compared to other additive manufacturing processes, statistical variations in part properties and the occurrence of defects cannot be avoided systematically. In this paper, a novel method for the inline assessment of part porosity is proposed in order to detect and to compensate for inherent limitations in the reproducibility of manufactured parts. The proposed approach is based on monitoring the parameter-specific decay of the optical melt pool radiance during the melting process, influenced by a time dependency of optical scattering within the melt pool. The underlying methodology compromises the regression of the time-dependent optical melt pool properties, assessed in visible light using conventional camera technology, and the resulting part properties by means of artificial neural networks. By applying deep residual neural networks for correlating time-resolved optical process properties and the corresponding part porosity, an inline assessment of the spatially resolved part porosity can be achieved. The authors demonstrate the suitability of the proposed approach for the inline porosity assessment of varying part geometries, processing parameters, and material aging states, using Polyamide 12. Consequently, the approach represents a methodological foundation for novel monitoring solutions, the enhanced understanding of parameter–material interactions and the inline-development of novel material systems in powder bed fusion of polymers.<br
Keywords: powder bed fusion; selective laser sintering; deep learning; deep neural network; process monitoring; quality control

Interaktion der Ausgangspulverkennwerte und der Belichtungsparameter im selektiven Laserstrahlschmelzen von Kunststoffen auf resultierende Bauteileigenschaften - Jaksch, Andreas; Wudy, Katrin; Drummer, Dietmar (16th Rapid.Tech, 2019)

Introduction to Powder and Beam Based Additive Manufacturing - Jaksch, Andreas; Cholewa, Simon; Bartels, Dominic; Markl, Matthias; Drummer, Dietmar (Progress in Powder Based Additive Manufacturing, 2025)
This chapter briefly describes the field of Additive Manufacturing, its benefits, and its applications. Furthermore, the used processes are introduced and explaine
Created from Fastlane, Scopus look-up

Kunststoffpulver für die Additive Fertigung: Vorhersage des Prozessverhaltens mittels prozessangepasster Analyse / Plastic powder for Additive Manufacturing: Prediction of process behavior based on process adapted characterization - Wudy, Katrin; Schmidt, Jochen; Lanzl, Lydia; Zhao, Meng; Jaksch, Andreas; Dechet, Maximilian; Hesse, Nicolas; Drummer, Dietmar; Peukert, Wolfgang (Vom Pulver zum multifunktionalen Bauteil, 2019)

Materialangepasste Prozessstrategien für das Lasersintern von Kunststoffen - Greiner, Sandra; Jaksch, Andreas; Drummer, Dietmar (27. Technomer - Fachtagung über Verarbeitung und Anwendung von Polymeren, 2021)
Das Lasersintern von Kunststoffen (LS) ermöglicht es Bauteile mit komplexen Geometrien ohne den Einsatz von Stützstrukturen und mit vergleichsweise hohen mechanischen Eigenschaften herzustellen. Aus diesen Gründen zählt es zu den vielversprechendsten additiven Fertigungstechnologien für die direkte Herstellung von individualisierten Bauteilen in der Kleinserie. In der Regel werden mittels LS teilkristalline Thermoplaste verarbeitet, da diese im Vergleich zu amorphen Werkstoffen höhere Bauteildichten erzielen. Um teilkristalline Thermoplaste erfolgreich zu verarbeiten, muss die Bauraumtemperatur auf ein materialspezifisches hohes Temperaturniveau gehoben werden, welches zwischen dem Beginn der Kristallisation und des Auf-schmelzens liegt. Der Laser bringt ortsselektiv die Energie zum Aufschmelzen der schichtabhängigen Bauteilquerschnitte ein, sodass bei einer Bauraumtemperatur zeit-gleich Schmelze und Pulver vorliegen können. Aus dieser Prozessführung ergeben sich hohe Temperaturen während der Bauphase, woraus die für das LS typischen hohen Abkühlzeiten und eine späte Bauteilverfügbarkeit resultieren. Es konnte nachgewiesen werden, dass unter quasi-isothermen Verarbeitungsbedingungen trotz des hohen Temperaturniveaus die Kristallisation und Erstarrung von Polyamid 12 wenige Schichten unterhalb der Pulverbettoberfläche erfolgt. Aus dieser Erkenntnis lassen sich neue Prozessstrategien für die Temperaturführung der Entnahmekammer ableiten, welche ein schnelleres Abkühlen von Bauteilen und die frühere Verfügbarkeit von Bauteilen ermöglichen. Als grundlegende Anforderung ist eine vergleichbare Temperaturhistorie aller Bauteile erforderlich. Entsprechend wird im Rahmen dieses Beitrags experimentell nachgewiesen, dass ein geometrieabhängiger Einfluss der Belichtung auf die vorherrschenden Temperaturfelder und Bauteileigenschaften besteht, welcher entweder im Rahmen der Standardprozessführung berücksichtigt werden muss oder durch materialangepasste fraktale Belichtungsstrategien vermieden werden kann. Anhand einer FEM-Simulation wird das Potential der Pro-zessbeschleunigung durch eine Anpassung des Baukammertemperiersystems mit lokal gesteuerter Abkühlung in z-Richtung dargestellt. Die entwickelten Strategien bieten die Möglichkeit einer Beschleunigung des LS-Prozesses sowie eine frühere Verfügbarkeit von Bauteilen mit gleichmäßigeren Bauteileigenschaften zu realisiere
Keywords: Additive Fertigung; Geometrieeinfluss; Temperaturkennwerte; Bauteileigenschaften; Belichtungsparameter; dynamische Abkühlstrategien; FEM-Simulation

Polybutylene terephthalate for laser-based powder bed fusion of polymers: processing constraints driven by zero-shear viscosity - Cholewa, Simon; Forstner, Thomas; Jaksch, Andreas; Drummer, Dietmar (Progress in Additive Manufacturing, 2025)
Laser-based powder bed fusion of polymers (PBF-LB/P) is a layer-based additive manufacturing (AM) method that produces functional components with superior mechanical properties. However, the limitation of commercially available materials, primarily polyamides, reduces the range of applications for PBF-LB/P processed parts. The use of novel polymer feedstocks, such as polybutylene terephthalate (PBT) in PBF-LB/P is of great interest, as the properties of PBT allow for an extension of the application of AM-built parts in the automotive and electronics sectors. Studies on the flowability of the powder under process conditions at evaluated temperatures showed a homogeneous surface of the powder bed. In addition, the processability of PBT powders in the PBF-LB/P process was investigated with a thermal camera, showing process limits for low-viscosity materials. Component properties showed a higher Young’s modulus than injection molding, while fracture behavior showed brittle behavior for the homo-PBT tested.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Additive manufacturing; Balling; Morphology; Powder bed fusion; Zero-shear viscosity

Polypropylene in laser-based powder bed fusion of polymers - Cholewa, Simon; Jaksch, Andreas; Drummer, Dietmar (PROCEEDINGS OF THE 38TH INTERNATIONAL CONFERENCE OF THE POLYMER PROCESSING SOCIETY (PPS-38), 2024)

Selektives Laserstrahlschmelzen von Kunststoffen: Lokale Bauteileigenschaften in Abhängigkeit unterschiedlicher Alterungszustände des Ausgangspulvers - Jaksch, Andreas; Hesse, Nicolas; Drummer, Dietmar; Schmidt, Jochen (6. Industriekolloquium des SFB 814, 2018)

Selektives Laserstrahlschmelzen von Polyamid 12 - Einfluss von Fließhilfsmitteln auf Verarbeitbarkeit und Bauteileigenschaften - Jaksch, Andreas; Hesse, Nicolas; Schmidt, Jochen; Drummer, Dietmar (Proceedings of the 17th Rapid.Tech Conference, 2021)

Structure Development of Semi-crystalline Polymers in Laser Based Powder Bed Fusion - Cholewa, Simon; Jaksch, Andreas; Drummer, Dietmar (Antec 2023, 2023)
The impact of melt hardening at low melt undercooling and under atmospheric pressure creates boundary conditions that have yet to be extensively studied since traditional techniques do not require such information. However, for powder bed fusion of polymers, the transition from the melt after exposure to an elastically dominant melt is critical as the crystallization in the building phase occurs under these conditions yielding stresses due to crystallization volume shrinkage. As a result, a process-adapted evaluation is required to determine how long the molten polymer remains viscously dominant, and the point where the stresses are stored in the melt. Therefore, the crystallization of a semi-crystalline melt is investigated in this work using rheological data in conjunction with FTIR microscopy. A modified measurement setup of the rheometer with an ATR crystal allows a simultaneous description of crystallization by FTIR spectroscopy and measurement of the rheological behavior of the material. A comparison between the different techniques indicates that the increase in viscoelastic properties during crystallization begins at low degrees of crystallinity. It is determined that the solidification of the melt is detectable at relatively low degrees of crystallization conversion, and that no stresses are accumulated in the material until this point.<br
Keywords: crystallization; FTIR spectroscopy; rheological behavior

Tailored Microstructure in Laser-Based Powder Bed Fusion of Polymers - Cholewa, Simon; Jaksch, Andreas; Drummer, Dietmar (Annual Technical Conference - ANTEC, Conference Proceedings, 2024)
Currently, the Laser-based powder bed fusion of polymers (PBF-LB/P) mainly uses polyamides, which prevents the components from exhibiting the mechanical characteristics of traditional manufacturing techniques. As a result, highly ductile and chemical-resistant materials are needed to cover more potential application areas. The preferred material is polypropylene (PP) with its various structures and settings. A common practice in conventional manufacturing processes is adjusting the morphology of the component, but studies examining this type of influence in PBF-LB/P are scarce. This work first introduces possible nucleation agents and subsequently, alongside the analytical investigation, manufactures components to assess the impact of the structure. It was concluded that processing the material is possible despite higher crystallization kinetics. For the first time, it was possible to process β -nucleated PP, demonstrated by the production of mechanical test specimens.
CRIS-Team Scopus Importer:2025-02-04

Tailored Syndiotactic Polypropylene Feedstock Material for Laser-Based Powder Bed Fusion of Polymers: Material Development and Processability - Cholewa, Simon; Stieglitz, Lucas; Jaksch, Andreas; Rieger, Bernhard; Drummer, Dietmar (ACS Applied Polymer Materials, 2023)
Current research on laser-based powder bed fusion of polymers (PBF-LB/P) is heavily focused on the relationship between the process and component properties of existing commercially available powder materials, thus constraining the scope of application. An innovative approach is presented in this study, which first emphasizes the synthesis of a tailored polypropylene for PBF-LB/P, and subsequently the performance of the synthesized polymer in the process. Syndiotactic polypropylene (sPP) was chosen because of its advantageous properties, such as low crystallinity and crystallization kinetics compared to isotactic polypropylene. Therefore, a well-known, highly active zirconocene dichloride catalyst was used with appropriate polymerization settings to yield moderately high-molecular-weight sPP with high syndiotacticity. As the obtained product already precipitated directly from the synthesis in particle form, no further intermediate process step to the feedstock material for PBF-LB/P was required. The obtained polymer was analyzed in terms of molecular weight, polydispersity, and syndiotacticity. Furthermore, key properties of the PBF-LB/P process, such as thermal properties, melt viscosity, and powder flow behavior, were investigated. The initial PBF-LB/P processability was assessed by building single layers in a parameter study using an EOS P 396 machine. Based on these findings, a multilayer component was manufactured demonstrating the processability of the material system.
Created from Fastlane, Scopus look-up
Keywords: additive manufacturing; crystallization; laser-based powder bed fusion of polymers; melting transition; polypropylene

Thin-Walled Part Properties in PBF-LB/P — Experimental Understanding and Nonlocal Material Model - Jaksch, Andreas; Spinola, Michele; Cholewa, Simon; Pflug, Lukas; Stingl, Michael; Drummer, Dietmar (SFF 2022, 2022)
Understanding the mechanics, geometry effects, and process behavior of thin-walled components is critical to fully realizing the potential of lightweight design in powder bed fusion of polymers (PBF-LB/P). In this work, parts built with rectangular cross sections of different sizes and orientations are described by their geometry, surface roughness, mechanical characteristics, and specific component geometry dependent on energy input. Experimental findings are supported by a nonlocal material model developed to adequately describe weakened material behavior at the surface of PBF-LB/P parts. This approach allows the simulation of the elastic modulus and density for complex part geometries while simultaneously considering boundary effects. Furthermore, the volume-surface ratio for thin-walled components were linearly correlated to the rectangular cross sections in different building orientations. This uniformity indicates that this ratio is a suitable quantity to consider. Therefore, the process knowledge is improved, especially in new design standards for thin-walled structures in PBF-LB/

Thin-Walled Part Properties in Powder Bed Fusion of Polymers—A Comparative Study on Temperature Development and Part Performance Depending on Part Thickness and Orientation - Jaksch, Andreas; Cholewa, Simon; Drummer, Dietmar (Journal of Manufacturing and Materials Processing, 2023)
To develop new areas of application for laser-based powder bed fusion of polymers (PBF-LB/P), a deeper process understanding of the resulting mechanical properties, particularly for thin-walled and complex structures, is needed. This work addresses the influence of part thickness and orientation in detail. For a general understanding, two PBF systems were used. For comparison, the normalized energy density was determined for specimens of various thicknesses and orientations. It could be seen that the normalized energy density exhibited opposing trends for the two systems for progressively thinner samples. During the process, the exposure temperature development was observed using an infrared camera for a greater understanding of the developing part properties. To further investigate the fracture behavior, an infrared camera was used during tensile testing, which revealed various patterns depending on the PBF-System used. The results showed a machine-dependent difference in the exposure temperatures and elongation at break for z-oriented parts. While the surface roughness was independent of the thickness, the density, porosity, and the mechanical properties were affected significantly by the part thickness. The parts showed a brittle breaking behavior with a crack initiation from the short side of the tensile bar. These results improved process expertise, and in particular the mechanical performance of thin-walled structures caused by temperature variations in PBF-LB/P.
Created from Fastlane, Scopus look-up
Keywords: mechanical properties; part properties; polyamide 12; powder bed fusion; thin walled

Understanding Cylinder Temperature Effects in Laser Beam Melting of Polymers - Greiner, Sandra; Jaksch, Andreas; Drummer, Dietmar (Lecture Notes in Mechanical Engineering, 2020)

Understanding geometry dependent part behavior of thin walled structures in powder bed fusion of polymers - Jaksch, Andreas; Cholewa, Simon; Drummer, Dietmar (Procedia CIRP, 2022)
To exploit the full potential of lightweight design of powder bed fusion of polymers (PBF- LB/P), it is necessary to identify the influence of nonstandard geometries and volume-surface ratios for thin wall structures, since research is still ongoing focused on typical process-component relationships using mainly standard dog-bone samples. For this purpose, different geometries with different volume-surface ratios are produced. To obtain a holistic understanding, it is necessary to describe the mechanical characteristics, geometry, and surface roughness, but also the energy input as a function of the specific components. In this study, the energy densities of the individual geometries is calculated using unique exposure strategy scan vectors. Within the scope of the performed work, the effect of the surface area to volume ratios on the mechanical performance of different geometries in PBF-LB is introduced. Furthermore, an influence on the surface roughness of the components in dependence of the geometry is observed. With these results, design guidelines are established for thin-walled structures in PBF-LB.
CRIS-Team Scopus Importer:2023-03-29
Keywords: design rules; thin walled components; volume-surface ratio